Revitalizing The Mother Tongue As An Effort To Form The Social Identity Of Elementary School Children - Meyqasari, Dwi (International Conference on Elementary Education, 2025)
This study aims to examine the role of mother tongue revitalization (regional language) in the formation of children's social identity in elementary schools and its potential to prevent cultural loss due to modernization and globalization. As the first language learned, the mother tongue plays a crucial role in shaping children's social and cultural identity. However, its use is increasingly declining, especially among younger generations who tend to prefer Indonesian or foreign languages in daily communication. This research employed a qualitative, descriptive narrative approach to explore the perspectives, experiences, and practices of teachers, parents, and students in elementary schools that incorporate regional languages into their curriculum. Data were collected through questionnaires, observations, and documentation. The findings indicate that revitalizing the mother tongue in elementary schools not only supports the preservation of regional languages but also strengthens children's social and cultural identity. The study highlights the need for more comprehensive education policies that prioritize the preservation of regional languages from an early age, ensuring that the cultural values embedded in mother tongues are maintained.